Variations of Root Canal Morphology in Permanent Anterior and Posterior Teeth Found in Indian Population: A Narrative Review - Rohit P. Magar; Sumanthini V. Margasahayam; Anuradha Patil; Divya Naik (Indian Journal of Dental Sciences)
Atypical tooth or root anatomy should be identified as a variation when it is observed frequently in a particular community or ethnic group. The root canal morphology depends on demographic factors such as age, gender, and ethnicity. There are differences in the morphology of the root canal that are inherent to different racial and ethnic groups. Knowing this helps clinicians understand root canal anatomy leading to better endodontic treatment outcomes. The studies reviewed had reported predominantly Vertucci type I in upper and lower anterior teeth. Considering the upper back region of the jaw, first and second premolars often had single-rooted type IV canals, followed by Vertucci type I and type III configurations. Mandibular premolars mainly featured type I canals. Maxillary molars typically had three roots, with the mesiobuccal (MB) root primarily classified as type I. Compared to second molars, first molars were more likely to have second MB canal. There are two roots found in mandibular molars; the first molar’s root that is distal was type I, and the proximal root was classified as type II. Accessory canals, including the middle mesial canal, were more prevalent compared to other populations, whereas C-shaped canals were relatively infrequent, varying from 7.53% to 13.12%. These results demonstrate the variety of root canal shapes, which can impact dental treatment approaches.